Assessment of Inpatient Satisfaction and Associated Factors at Hai Phong International General Hospital in 2025 - Thi Hang, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Objective: This study aimed to assess inpatient satisfaction and identify associated factors at Hai Phong International General Hospital in 2025. Methods: A cross-sectional descriptive study was conducted among 385 inpatients selected by convenience sampling. Data were collected using the standardized patient satisfaction questionnaire issued by the Ministry of Health under Decision No. 56/QD-BYT (2024). Statistical analyses, including descriptive statistics and logistic regression, were performed using SPSS 22.0 to determine factors associated with overall patient satisfaction. Results: The overall inpatient satisfaction rate was 96.4%. Both univariate and multivariate analyses indicated that the treatment department was the only factor significantly associated with overall satisfaction (p<0.05), with patients in the Orthopedic Surgery Department reporting lower satisfaction levels compared to other departments (OR=0.444). Demographic characteristics such as gender, age, education level, occupation, and length of stay were not significantly associated with satisfaction. Conclusion: Inpatient satisfaction at the hospital was remarkably high. However, differences among departments particularly the lower satisfaction in the Orthopedic Surgery Department highlight the need to enhance postoperative care and rehabilitation support. Keywords: Patient satisfaction; inpatients.